2016
DOI: 10.3892/mmr.2016.5178
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin ameliorates ventricular remodeling via the TGF-β1 signaling pathway in rats following myocardial infarction

Abstract: Statins are widely used in patients with cardiovascular diseases. A considerable number of previous studies revealed that the intracellular signaling of transforming growth factor (TGF)-β1 mediated the development of cardiomyocyte hypertrophy and interstitial fibrosis. However, whether statins can ameliorate ventricular remodeling in post-myocardial infarction via the TGF-β1 signaling pathway remains to be rigorously tested. The left anterior descending artery was ligated to induce a rat model of myocardial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Smad2/3 is one of the main downstream effectors of TGF- β 1 [ 37 ]. Previous studies have reported that inhibition of TGF- β 1/Smad2/3 signaling effectively protects against cardiomyocyte apoptosis and detrimental ventricular remodeling [ 37 39 ]. The in vitro experiment also suggested that the increased production of collagen I and collagen III as well as excessive proliferation of CFs induced by Ang II was attenuated through suppression of TGF- β /Smad signaling [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Smad2/3 is one of the main downstream effectors of TGF- β 1 [ 37 ]. Previous studies have reported that inhibition of TGF- β 1/Smad2/3 signaling effectively protects against cardiomyocyte apoptosis and detrimental ventricular remodeling [ 37 39 ]. The in vitro experiment also suggested that the increased production of collagen I and collagen III as well as excessive proliferation of CFs induced by Ang II was attenuated through suppression of TGF- β /Smad signaling [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maejima and colleagues demonstrated that telmisartan, a partial PPAR- γ agonist, could reduce TGF- β 1 expression post-MI by activating PPAR- γ in the noninfarcted myocardium in rats [ 28 ]. TGF- β 1 plays an important role in the development cardiac fibrosis [ 29 ]. The canonical TGF- β 1 and Smad2/3 signaling pathway can promote ECM production in Ang II-stimulated CFs; however, the PPAR- γ agonist curcumin could suppress ECM production by activating PPAR- γ [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…TAK1 is a mitogen-activated protein kinase kinase kinase (MAPKKK) downstream of TRAF6 [ 32 , 33 ]. Therapies that limit fibrosis have been shown to decrease TAK1 expression, consistent with its role in signaling [ 29 ]. Since Ghrelin upregulated PPAR- γ expression, we further explored the in vitro and in vivo linkage between Ghrelin and TGF- β 1 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The AMI and ET groups were subjected to permanent ligation of the left anterior descending coronary artery (LAD), using a 6-0 suture thread to induce myocardial infarction. (9) Under deep anesthesia [ketamine (10 mg/kg body weight)], the thorax was incised at the third intercostal space, and the LAD was ligated 2 mm below the left atrium. Occlusion of the LAD was confirmed microscopically by discoloration of the ischemic area below the ligature.…”
Section: Methodsmentioning
confidence: 99%